EKSPLORASI STRATEGI PEDAGOGIK GURU DALAM MENGATASI HAMBATAN KETERBATASAN AKSES SARANA PEMBELAJARAN STUDI KASUS SDN 21 BIAU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Rahma S. Kadir. Pedagogical strategies in overcoming learning barriers in developing areas (Case Study of SDN 21 Biau). Thesis, Elementary School Teacher Education, Faculty of Teacher Training and Education, Madako University. Supervisor 1 Hamna, Supervisor 2 Hasia Marto. This study aims to describe teachers' pedagogical strategies in overcoming learning obstacles and their effectiveness in improving the quality of learning at SDN 21 Biau. The method used was descriptive qualitative with a case study approach. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, namely through data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers at SDN 21 Biau apply various adaptive pedagogical strategies to overcome limited facilities and infrastructure, such as the unavailability of internet, lack of books, and the school's geographical conditions which are prone to flooding. Teachers implement a contextual and constructivist approach by utilizing the surrounding environment as a learning resource, using lecture methods, questions and answers, storytelling, and giving assignments that are relevant to students' lives. This strategy has proven effective in increasing student engagement, motivation, and understanding, even in limited learning conditions. Thus, teachers' pedagogical strategies at SDN 21 Biau are able to create meaningful learning and foster students' enthusiasm for learning in developing areas.